Tratamiento informativo sobre el trabajo infantil en los noticieros televisivos: estudio de caso Ecuavisa - Topón Puga, Jefferson Fabián (2020)
Title: Information Treatment on Child Labor (CL) in the Newscasts: Ecuavisa case study Mass media are a tool for widespread of information. Its speed and dynamism enable society to keep updated on national and international political, economic, and social development. Television, being one of the most popular mass medium, is able to persuade audiences and brings out social changes. Hence, the present research analyzes the representation of child labor in the press notes on the TV program “Televistazo” of Ecuavisa channel station. This inquiry is based on three objectives oriented to know the treatment, journalistic approach, and frequency notes emission on CL. It is based on theories, concepts and characteristics of journalistic work regarding the presence of children in the mass media. Human rights issues of the vulnerable social groups and articles of different laws, regulations and normative regulations such as the Constitution of the Republic, the Criminal Code, the Children's and Teenagers' Code and the Communication Organic Law. were also evaluated. In addition, the Code of Ethics and the Ecuavisa Communication Guide were used. The selection of concepts and research models were carried out with the bibliographic review of several authors who proposed studies on CL and the media. The study is based on a qualitative approach, through a technique of sampling by convenience, with which thirteen journalistic notes broadcast on Televistazo from 2012 to 2019 were selected. They were reported in June when Children's Day and the Day of the Fight against Child Labor is celebrated and in December when child labor increases due to the Christmas and New Year´s eve holidays. It should be stated that during the month of December 2019, the news program Televistazo was followed daily from Monday to Friday from 7:00 p.m. to 8:00 p.m. For data analysis, an observation sheet was applied based on four indicators that made it possible to know whether CL is treated as a subject of public and political interest that affects society as a whole. It was verified whether the journalistic notes are supported by the regulations that protect the rights of children and teenagers and grant their participation as an active source for the development of the news. Thus, it was demonstrated that child labor is not an issue that is frequently seen in the media. Also, it was determined that 31% of the press notes issued, the youngsters are not treated as the protagonists of the CL facts. Neither journalists interview or talk with them about this problem. Consequently, this concern has remained throughout the years.